Vermicomposting Kitchen, Municipal Market and Tea Factory Waste using EiseniaFetida Earthworms - M, Mochache; R, Yegon; O, Ngetich (International Journal of Environment, Agriculture and Biotechnology, 2019)
Population increase, urbanization, industrialization and agricultural activities result in accumulation of solid waste. This waste requires sustainable management through techniques such as vermicomposting. The study aimed at determining the rate of vermicomposting of kitchen, municipal market and tea factory waste using Eisenia fetida earthworm species at the University of Embu, Kenya. The study was arranged in completely randomized design replicated thrice. Data was collected on decomposition rate, carbondioxide evolution, earthworm count, nutrient content of vermicompostedwaste and days to vermicompost maturity. SAS version 9.4softwarewas used for statistical data analysis. Treatment means were separated using least significant difference (l.s.d.) at p≤0.05 probability level. Kitchen waste vermicompost had the fastest decomposition rate of 0.6 kg/day. Carbondioxide evolution analysis was done weekly whereby a value of 0 µgCO2/g vermicompost/m2/day was recorded at week 15 when the vermicomposts had stabilized. Kitchen and market waste vermicompostshad the highest earthworm countof 169 and 153, respectively.The nutrient contents of the three vermicomposts were not significantly different. The study concluded that kitchen waste had the highest vermicomposting rate as well as earthworm count. Therefore, the study recommends that kitchen waste and market waste can be used where the aim of vermicomposting is earthworm production.